2010
DOI: 10.1007/bf03256359
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Common -866G/A Polymorphism of the Uncoupling Protein 2 Gene on Weight Loss and Body Composition under Sibutramine Therapy in an Obese Taiwanese Population

Abstract: By comparing the placebo and sibutramine groups with ANCOVA, our data showed a strong effect of sibutramine on weight loss in the combined UCP2 -866 AA + GA genotype groups (p < 0.001). Similarly, a strong effect of sibutramine on body fat percentage loss was found for individuals with the AA or GA genotypes (p < 0.001). In contrast, sibutramine had no significant effect on weight loss (p = 0.063) or body fat percentage loss (p = 0.194) for individuals with the wild-type GG genotype, compared with the placebo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…In conclusion, our findings support the hypothesis that ADIPOQ rs266729 may help predict weight reduction and fat loss in response to sibutramine therapy together with other markers found in some previous studies 37. Independent replications are needed to confirm the role of the ADIPOQ rs266729 polymorphism found in this study.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In conclusion, our findings support the hypothesis that ADIPOQ rs266729 may help predict weight reduction and fat loss in response to sibutramine therapy together with other markers found in some previous studies 37. Independent replications are needed to confirm the role of the ADIPOQ rs266729 polymorphism found in this study.…”
Section: Resultssupporting
confidence: 90%
“…Our previous findings6,7 mainly reported of the association studies of sibutramine with the GNB3 rs5443 and UCP2 rs659366 polymorphisms. In this work, we extended the previous research to test the hypothesis that ADIPOQ rs266729 may influence weight loss and fat change in response to sibutramine treatment amongst Taiwanese obese individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Two other studies reported that in obese children with the A/A genotype the resting energy expenditure was increased [47], and in Pima Indians the SNP was associated with increased 24-hour energy expenditure [48]. A recent study reported a strong effect of sibutramine on weight and body fat percentage loss in the combined UCP2 A/A + G/A of the SNP G(−866)A in a Taiwanese population [49]. Interesting to note that in their placebo group, the A/A genotype showed the least weight and fat percentage loss, which was in agreement with a study conducted in Korean women [46], indicating that the effect of the UCP2 G(−866)A polymorphism might be universal, at least for Asian.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, Hsiao et al57 used the same patients in which they had investigated the role of GNβ3 polymorphism54 to study the role of −866G/A polymorphism on weight loss in patients treated with sibutramine. The uncoupling protein 2 (UCP2) gene encodes a mitochondrial transporter protein, which is highly expressed in adipose tissue, skeletal muscle, and pancreatic islets 58.…”
Section: Predictors Associated With Sibutramine Treatmentsmentioning
confidence: 99%